Scalp involvement in pemphigus: a prognostic marker - Sar-Pomian, Marta; Konop, Marek; Gala, Kamila; Rudnicka, Lidia; Olszewska, Malgorzata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Scalp involvement in the course of pemphigus is observed in 16–60% of patients. Aim : To determine the prognostic significance of scalp involvement in pemphigus vulgaris and pemphigus foliaceus. Material and methods : A total of 75 patients (46 with pemphigus vulgaris, 29 with pemphigus foliaceus) were included into this prospective study. The following clinical data were analyzed: Pemphigus Disease Area Index, time to complete clinical remission and duration of complete clinical remission. Indirect immunofluorescence and enzyme-linked immunosorbent assay were performed to monitor serum pemphigus antibodies. Results : Scalp involvement was observed in 30/46 (65.2%) patients with pemphigus vulgaris and 28/29 (96.6%) patients with pemphigus foliaceus. A positive correlation was found between scalp involvement and general disease severity as measured by the Pemphigus Disease Area Index (r = 0.7, p < 0.05). The time required to achieve a complete clinical remission in patients with and without scalp involvement was 39.1 ±47.1 and 9.1 ±7.8 months, respectively. The duration of complete clinical remission was 14.1 ±17.4 and 105.7 ±108.8 months, respectively. The respective time required to achieve serological remission was 37.7 ±58.5 and 15.5 ±18.8 months, whereas the duration of serological remission was 9.2 ±18.8 and 39.1 ±60.1 months, respectively. The average concentration of anti-desmoglein 1 autoantibodies was significantly higher in patients with scalp involvement compared to patients without scalp involvement (109.9 ±68.0 U/ml and 21.3 ±39.4 U/ml). Conclusions : Scalp involvement in pemphigus is associated with a higher disease severity, longer time required to achieve complete clinical and serological remission and may indicate the need for a more aggressive therapeutical approach.